Salinity effect on growth and toxin production of four tropical Alexandrium species (Dinophyceae) - Lim, Po Teen; Ogata, T. (Elsevier Ltd., 2005)
Four tropical PSP toxins-producing dinoflagellates, Alexandrium minutum, Alexandrium tamiyavanichii, Alexandrium tamarense and Alexandrium peruvianum from Malaysian waters were studied to investigate the influences of salinity on growth and toxin production. Experiments were conducted on constant temperature 25 8C, 140 mE mol mK2 sK1 and under 14:10 light:dark photo-cycle with salinity ranged from 2 to 30 psu. The PSP-toxin congeners, GTX 1–6, STX, dcSTX, NEO and C1–C2 were analysed by high performance liquid chromatography. Salinity tolerance of the four species in decreasing order is A. minutumOA. peruvianumOA. tamarenseOA. tamiyavanichii. Specific growth rates and maximum densities varied among these species with A. minutum recorded as the highest, 0.5 dayK1 and 6!104 cells mLK1. Toxin content decreased with elevated salinities in A. minutum, the highest toxin content was about 12 fmole cellK1 at 5 psu. In A. tamiyavanichii, toxin content peaked at optimal growth salinity (20 and 25 psu). Toxin content of A. tamarense, somehow peaked at sub-optimal growth salinity (15 and 30 psu). Results of this study implied that salinity fluctuation not only influenced the growth physiology but also toxin production of these species.